A Combined Computational and Experimental Study on Nanoparticle Transport and Partitioning in the Human Trachea and Upper Bronchial Airways - Jiawei Ma; Wei-Chung Su; Yi Chen; Yidan Shang; Jingliang Dong; Jiyuan Tu; Lin Tian (Aerosol and Air Quality Research)
Abstract In the past few decades, the transport and deposition of aerosol in the human respiratory tract has been a crucial area of research, resulting in the identification of the toxicity pathways of inhaled pollutants and facilitating the design of efficient drug delivery systems for targeted treatment. Owing to the complexity of the tracheobronchial tree, experimental studies in vivo/in vitro have been extremely limited; hence, detailed data on the airflow and particle dynamics have been obtained predominantly through computational investigations. With rapid advances in medical imaging and computational capacities, sophisticated human tracheobronchial trees that include the 6th, 7th or 15th generation have been increasingly described in the literature. However, continued progress in anatomical reconstruction and mathematical idealized modeling, the two most frequently employed approaches to airway modeling, requires a detailed fundamental analysis on the morphology-induced sensitivity of particle-flow partitioning, and particle deposition in the airways. This study combined numerical and experimental investigations on the transport, deposition and partitioning of nanoparticles in the upper tracheobronchial airways. An anatomically realistic airway was reconstructed via CT scans, and a simplified numerical model was developed that incorporated physical irregularities in the trachea and assessed new boundary conditions to simulate air partitioning in the lobar bronchi, and flow and particle dynamics. An experiment measuring the penetration and deposition of sodium chloride (NaCl) nanoparticles in the anatomical and idealized airway models was conducted in parallel, and the results were compared with the computational predictions.